LINEAR APPROXIMATION FOR INTENSITIES OPTIMIZATION PROBLEM OF SEQUENTIAL-PARALLEL EXECUTION OF INTERSECTING OPERATION SETS - G. M. Levin; B. M. Rozin; A. B. Dolgui (Informatika)
The mathematical model and method for the problem of optimization of intensities of sequen-tial-parallel execution of intersecting operation sets are proposed. The proposed method is based on the approximation of the problem by linear programming problem.